Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3dt51233a
|View full text |Cite
|
Sign up to set email alerts
|

Thallophilic interactions and Tl–aryl π-interactions are competitive with cation–cation repulsion: [LTl2L]2+ dications as salts of weakly co-ordinating anions

Abstract: The synthesis and characterization by single-crystal X-ray diffraction of two thallium salts of the non-co-ordinating anion [B{3,5-(CF3)2C6H3}4] are reported. They possess Tl-Tl contacts supported by Tl-aryl interaction. This cation association overcomes both electrostatic repulsion and cation-anion size and charge matching considerations in the [LTl2L](2+) dications so formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
20
1
1
Order By: Relevance
“…These isomer shifts and quadrupole splittings are consistent with low-spin Fe II , and as such we assign this site to the low-spin center of an [Fe HS -Fe LS ] species. 56 Upon further decreasing temperature to 80 K, we observed the continuation of this trend, revealing the additional decrease of the high-spin Fe II site in [Fe HS -Fe HS ] to 31(10) and 36(7)% for 3 and 4, respectively, whereas both the high-and low-spin Fe II sites in [Fe HS -Fe LS ] increased to 33(1) and 35(11)% for 3 and 31(1) and 33(8)% for 4, respectively. Moreover, in the cases of 1 and 2, the data were best fit considering only two quadrupole doublets each, corresponding to the high-and lowspin centers of an [Fe HS -Fe LS ] species, with no evidence for [Fe HS -Fe HS ].…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These isomer shifts and quadrupole splittings are consistent with low-spin Fe II , and as such we assign this site to the low-spin center of an [Fe HS -Fe LS ] species. 56 Upon further decreasing temperature to 80 K, we observed the continuation of this trend, revealing the additional decrease of the high-spin Fe II site in [Fe HS -Fe HS ] to 31(10) and 36(7)% for 3 and 4, respectively, whereas both the high-and low-spin Fe II sites in [Fe HS -Fe LS ] increased to 33(1) and 35(11)% for 3 and 31(1) and 33(8)% for 4, respectively. Moreover, in the cases of 1 and 2, the data were best fit considering only two quadrupole doublets each, corresponding to the high-and lowspin centers of an [Fe HS -Fe LS ] species, with no evidence for [Fe HS -Fe HS ].…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…55 Here, the site with a smaller ΔE Q was shown to correspond to the [Fe HS -Fe LS ] complex, stemming from the distortion of the high-spin Fe II coordination sphere imposed by spin crossover of the second Fe II center. 55a,56 Finally, the third doublet, which accounts for 34(1), 33(2), 19(2), and 19(1)% of the spectra for 1−4, respectively, exhibits parameters of δ = 0.44(1)−0.45(1) mm/s and ΔE Q = 0.45(1)−0.62(2) mm/s (blue lines in Figure 5). These isomer shifts and quadrupole splittings are consistent with low-spin Fe II , and as such we assign this site to the low-spin center of an [Fe HS -Fe LS ] species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…15 The studies on 1 consist of single point calculations using the crystal structure. 6 Ab initio calculations on the model system were performed at the CCSD(T) 16 , BD 17 , MP2 18 and SCS-MP2 19 levels. In all wavefunction calculations reported here, all 21 valence electrons of the Tl atoms were correlated.…”
Section: Methodsmentioning
confidence: 99%
“…Calculations on systems with aurophilic bonds suggest that these relativistic effects provide at least 15% of the aurophilic attraction. 5 Metallophilic bonds involving thallium atoms (thallophilic), one of which was the subject of a recent experimental study, 6 have been observed at distances between 3.4-3.8 Å. 7 In comparison, twice the van der Waals and covalent radii of Tl are 3.92 Å and 2.96 Å, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation